«May God guard you and give you much strength for scientific work»: A. V. Florovsky and Belarusian Slavic studies in Vilno of the second half of the 1930s - Bukharin, Mikhail D. (Journal of the Belarusian State University. History, 2022)
By the middle of 1930s, largely due to the efforts of Russian emigrant scholars, Prague became a major center of the studies in Slavic history, in particular in the history of Czech cultural ties with other major centers of Slavic culture in the East. Russian historian A. V. Florovsky in the mid – second half of the 1930s worked on a number of studies on the history of Slavic culture. To a large extent, his research efforts were aimed at reconstructing the biography of the Belarusian enlightener F. Skoryna. There are some important materials in the Archive of the Russian Academy of Sciences that allow reconstructing the course of A. V. Florovsky’s research on the history of cultural contacts of several centers of Slavic culture – Vilna, Prague, Moscow – letters to him from Belarusian Slavists A. I. Lutskevich, V. I. Samoilo, F. Ilyashevich and V. Tolochko. The corpus of these sources on the history of Belarusian Slavic studies was supplemented by attribution of a previously unknown letter by A. I. Lutskevich. The complex of these materials made it possible to clarify the date of compilation and identify the manuscript of one of the articles by A. V. Florovsky «Initial stages of the development of printing among the Eastern Slavs». Letters from Belarusian Slavists to A. V. Florovsky show the mechanism of work of historians in conditions of strict political separation of Europe, separation from libraries and archival collections, discussion of important scientific hypothesis. The end of these contacts was put by a sharp change in the political situation in Eastern Europe in 1939–1940.
Keywords: Slavic studies; Belarusian science in emigration; Eastern Europe; Central Europe; F. Skoryna; A. V. Florovsky; Prague